Integrating GIS and Multi-Criteria Decision Making for Sustainable Industrial Waste-to-Energy Planning - Shahin Alom Shobuj; Robin Mia (International Journal on Orange Technologies, 2021)
Industrial waste-to-energy (WtE) systems have gained increasing attention as sustainable solutions for addressing the dual challenges of growing industrial waste generation and rising energy demand. This study proposes an integrated Geographic Information System (GIS) and Multi-Criteria Decision-Making (MCDM) framework for prioritizing and siting WtE facilities under energy security and environmental sustainability constraints. The framework combines spatial analysis with systematic decision-support techniques to evaluate technical, environmental, economic, and socioeconomic factors influencing WtE project feasibility. GIS is employed to analyze spatial parameters, including land use, transportation accessibility, waste generation patterns, population density, topography, and environmental sensitivity, enabling the identification of suitable locations for WtE development. To improve decision accuracy and transparency, the Analytical Hierarchy Process (AHP) and Fuzzy Analytical Hierarchy Process (FAHP) are integrated to assign weighted priorities to evaluation criteria while addressing uncertainty and subjective expert judgment. The proposed approach generates suitability maps that classify candidate sites according to sustainability and operational performance. Environmental considerations such as soil stability, proximity to water bodies, and ecological risk are incorporated alongside economic and social indicators, including cost-effectiveness, energy recovery potential, logistics efficiency, and community acceptance. The framework also supports supply-chain optimization by reducing transportation costs and associated greenhouse gas emissions. Overall, the GIS–MCDM approach enhances the reliability and effectiveness of WtE planning, contributing to renewable energy generation, landfill reduction, circular economy development, and long-term sustainable industrial growth.